Occult Bacteraemia and Aortic Graft Infection: A Wolf in Sheep’s Clothing - E. Trautt; S. Thomas; J. Ghosh; P. Newton; A. Cockcroft (Case Reports in Vascular Medicine)
We report a case of late-onset aortic prosthetic vascular graft infection. We stress the importance of maintaining a high index of suspicion for any patient presenting with fever on the background of in situ prosthetic material. We present the difficulties in managing these extremely complicated, often life and limb threatening infections and suggest that a multidisciplinary team approach, involving specialist centre referral, may be key to success. We highlight the difficulties in diagnosing late-onset PVGI, where presentation can be subacute with subtle signs and confusing microbiology. In this case the presentation was pyrexia of unknown origin with multiple positive blood cultures isolating a variety of gut-associated organisms; a wolf in sheep’s clothing.